Cover Image. (18th October 2018) - Li, Lianfu; Zhang, Xin; Luan, Zhendong; Du, Zengfeng; Xi, Shichuan; Wang, Bing; Cao, Lei; Lian, Chao; Yan, Jun
Abstract : The cover image is based on Research Article Raman vibrational spectral characteristics and quantitative analysis of H2 up to 400°C and 40 MPa by Lianfu Li et al., https://doi.org/10.1002/jrs.5420 .